Autism spectrum disorder phenotypes and prenatal exposure to methylmercury - van Wijngaarden, Edwin; Davidson, Philip W; Smith, Tristram H; Evans, Katie; Yost, Kelley; Love, Tanzy; Thurston, Sally W; Watson, Gene E; Zareba, Grazyna; Burns, Christine M; Shamlaye, Conrad F; Myers, Gary J (Epidemiology (Cambridge, Mass.), 2013)
There continues to be public concern that mercury exposure and autism spectrum disorder (ASD) may be associated. The primary source of exposure to organic mercury in humans is to methylmercury from fish consumption. We evaluated the association between prenatal methylmercury exposure and ASD phenotype in children and adolescents in the Republic of Seychelles, where fish consumption is high. We administered the Social Communication Questionnaire to parents of a cohort of 1784 children, adolescents, and young adults. The Social Responsiveness Scale was administered to teachers of 537 cohort subjects at about 10 years of age. Prenatal exposure to methylmercury was measured in maternal hair samples collected at or near the time of birth. Multivariable regression models evaluated the relationship between prenatal methylmercury exposure and ASD phenotypic scores, adjusting for relevant covariates. The mean prenatal methylmercury exposure for subjects in the analysis was 8.4 ppm (standard deviation [SD] = 5.7). The mean Social Communication Questionnaire score was 8.0 (SD = 4.4). The mean prenatal methylmercury exposure for subjects with Social Responsiveness Scale scores was 6.7 ppm (SD = 4.4) and the mean Social Responsiveness Scale score was 57.6 (SD = 26.8). No consistent association between prenatal methylmercury exposure and ASD screening instrument was found, using linear and nonlinear regression analyses. Prenatal exposure to methylmercury was not associated with ASD phenotypic behaviors in our cohort of high fish consumers. Our findings contribute to the growing literature suggesting that exposure to methylmercury does not play an important role in the development of ASD phenotypic behavior.